2022
DOI: 10.1029/2021jg006617
|View full text |Cite
|
Sign up to set email alerts
|

Canopy Temperature Is Regulated by Ecosystem Structural Traits and Captures the Ecohydrologic Dynamics of a Semiarid Mixed Conifer Forest Site

Abstract: Canopy temperature differed significantly among different tree density and height classes at a semiarid mixed conifer forest site • Diurnal canopy temperature dynamics were closely related to canopy photochemical reflectance and sap flow • Satellite observations from ECOsystem Spaceborne Thermal Radiometer Experiment on Space Station captured key aspects of diurnal canopy temperature dynamics and were consistent with site-level data Supporting Information:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 75 publications
1
18
0
Order By: Relevance
“…García-Tejero et al ( 2018) and Pou et al (2014) conducted studies on almonds and grapevines, respectively, using thermography and observed that plants subjected to water restriction conditions had higher T canopy . However, variations in meteorological variables can also directly influence the T canopy data (Javadian et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…García-Tejero et al ( 2018) and Pou et al (2014) conducted studies on almonds and grapevines, respectively, using thermography and observed that plants subjected to water restriction conditions had higher T canopy . However, variations in meteorological variables can also directly influence the T canopy data (Javadian et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…7). Such observations are also consistent with many previous findings respectively made using EC (Duman et al ., 2021; Javadian et al ., 2022), proximate remote sensing (Still et al ., 2021; Yang et al ., 2021), and satellite (Lian et al ., 2017; Duveiller et al ., 2018) measurements. The widespread presence of ∆ T variability further suggests that the conventional approach of using T a alone for inferring T c could produce large uncertainty.…”
Section: Discussionmentioning
confidence: 99%
“…This can be caused by the effect of canopy structure (e.g. self‐shading and canopy gaps) and microclimate, but has not been explored comprehensively (Pau et al ., 2018; Javadian et al ., 2022). Thus, it is reasonable to expect that there are scale‐dependent mechanisms in regulating plant thermoregulation capability.…”
Section: Discussionmentioning
confidence: 99%
“…UAV-borne thermal sensors might possess the ability to detect increase in subdegree temperature caused by stress or disease progression at tree-level [25]. Additionally, thermal sensors also help in assessing water stress in vegetation [29]. RGB sensors have been used to measure vegetation height as well as to compute Normalized Green Red Difference Index (NGRDI), visible atmospherically resistant index (VARI), and Green Leaf Indices (GLIx) [30,31].…”
Section: Need For Low-cost Uav-based Monitoring Systemsmentioning
confidence: 99%